1996
DOI: 10.1248/bpb.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Covalently Bound Hypusine and Deoxyhypusine to Protein Using Submilligram of Protein Samples by HPLC.

Abstract: A sensitive and reliable method for the determination of hypusine and deoxyhypusine in eIF-5A protein, an initiation factor of protein synthesis, was developed. An advantage of this method is the use of N epsilon-(5-aminopentyl)lysine, an analogue of deoxyhypusine, as an internal standard. The application made it possible to determine hypusine in less than a mg of protein samples from cultured HTC cells and rat organs. After acid hydrolysis of protein samples to which had been added the internal standard, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Then, SDS\PAGE and fluorography were performed as described by Laemmli [34] and Laskey and Mills [35] respectively, using 100 µg of protein of the 100 000 g supernatant. Furthermore, hypusine in eIF5A was measured directly by reversed-phase HPLC with a fluorescence detection of o-phthalaldehyde using 1 mg of protein from the 100 000 g supernatant, as described previously [36].…”
Section: Measurement Of the Amount Of Eif5a And The Level Of Hypusinementioning
confidence: 99%
“…Then, SDS\PAGE and fluorography were performed as described by Laemmli [34] and Laskey and Mills [35] respectively, using 100 µg of protein of the 100 000 g supernatant. Furthermore, hypusine in eIF5A was measured directly by reversed-phase HPLC with a fluorescence detection of o-phthalaldehyde using 1 mg of protein from the 100 000 g supernatant, as described previously [36].…”
Section: Measurement Of the Amount Of Eif5a And The Level Of Hypusinementioning
confidence: 99%
“…This analytical method can replace previous HPLC methods with retention times detecting the orthophthaldialdehyde derivatives of deoxyhypusine at 17.4 min and hypusine at 17.4 min (Beppu et al 1996;Beninati et al 1990). Moreover, reproduction of these experiments showed that a gradient performed with mobile phase A consisting of 20 mM sodium acetate and mobile phase B consisting of 40% methanol and 40% acetonitrile prolonged retention times of deoxyhypusine to 58.55 min and hypusine to 50 min (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…N-Epsilon-(5-aminopentyllysine) which is a structural analogue of deoxyhypusine was used as an internal standard. This separation resulted in retention times of deoxyhypusine with 17.2 min and for hypusine with 14.4 min, respectively (Beppu et al 1996) dependent on the gradient being used. However, reproduction of these experiments proved that the imine derivatives showed non-reproducible stabilities (Kaiser et al unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…16) HTC cells were grown as either a monolayer in culture dishes or a suspension in spinner flasks. HTC cells were maintained in Swim's S-77 medium containing 10% newborn bovine serum.…”
Section: )mentioning
confidence: 99%